Desquamative Interstitial Pneumonitis in a Healthy Non-Smoker: A Rare Diagnosis - Ryan R Kroll; Diane A Flood; John Srigley (Canadian Respiratory Journal)
This article reports a rare condition first described in 1965 and is most commonly associated with smoking and certain occupations. Onset of nonspecific symptoms is typically insidious and, while bloodwork and imaging may be valuable, tissue sampling is required for diagnosis. Desquamative interstitial pneumonitis most commonly affects tobacco smokers in their fourth or fifth decades of life; this article, however, describes the condition in a 27-year-old who worked in a potato chip factory.